Assessing Daylighting Conditions and Strategies in Residential Workspaces During the COVID-19 Pandemic: A Case Study of Apartment Buildings in Malaysia (International Journal of Built Environment and Sustainability, 2025)
Incorporating daylighting strategies in buildings is crucial for enhancing visual conditions, energy efficiency, and productivity. Working in an environment without windows or with limited access to daylight can negatively affect performance and lead to eye fatigue, stress, and headaches. The COVID-19 pandemic and the rapid development of IT capabilities have resulted in an increase in home-based workspaces worldwide, including Malaysia. This emerging trend, accelerated by the pandemic, has prompted people to work from their homes. Therefore, it is essential to ensure visual comfort for home workers by implementing effective daylighting strategies in their residential work environments. This study focuses on evaluating daylighting conditions in existing residential apartment buildings (RABs) in Malaysia, particularly considering their transformation into workspaces during the COVID-19 outbreak. The research methodology consists of three sequential steps; selecting and observing case studies, conducting simulation experiments, and administering a questionnaire survey. Hence, it involved observing 10 contemporary RABs in Johor Bahru, recording their facade and layout characteristics, including window shading. Then, simulation experiments were conducted by the IES-VE software to demonstrate indoor daylighting condition. Additionally, a questionnaire survey was conducted from 360 occupants of the selected RABs, utilizing multiple-choice questions and a five-point Likert scale. The collected data was analyzed using descriptive statistics. The results revealed that the lack of external window shading forced residents to rely on internal shading methods. Moreover, excessive tropical sunlight resulted in visual discomfort and glare issues for users. However, occupants predominantly utilized conventional shading options, such as curtains, leading to poorly illuminated indoor environments and increased reliance on artificial lighting for desk-related tasks. The significant findings from this research emphasize the design of flexible spatial layouts with ample open spaces along with the use of efficient internal and external shading devices in RABs, to create well-lit and healthy working environments.
Keywords: Daylight, Visual comfort, COVID-19, Shading device, Glare.